2020
DOI: 10.3390/ma14010040
|View full text |Cite
|
Sign up to set email alerts
|

Does the Addition of Zinc Oxide Nanoparticles Improve the Antibacterial Properties of Direct Dental Composite Resins? A Systematic Review

Abstract: A promising approach to improve the poor antibacterial properties of dental composite resins has been the addition of metal oxide nanoparticles into the resin matrix. This systematic review aimed to determine whether the addition of zinc oxide nanoparticles (ZnO-NPs) improves the antibacterial properties of direct dental composite resins. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered with the PROSPERO datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…However, a higher annual failure rate has been reported for posterior composite resin restorations than for amalgam restorations, which is attributed primarily to secondary caries ( Kopperud et al, 2012 ; Opdam et al, 2014 ; Astvaldsdottir et al, 2015 ). Generally, secondary caries occur on the tooth after composite resin filling because oral biofilm bacteria are more likely to accumulate on the surface of resin restorations, leading to demineralization of dental hard tissues due to acid production, thus destroying the tooth structure and further providing a way for bacterial invasion ( Arun et al, 2021 ). Since secondary caries limit the lifetime of composite resin, it is urgent to endow composite resin with antibacterial properties and remineralizing capability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a higher annual failure rate has been reported for posterior composite resin restorations than for amalgam restorations, which is attributed primarily to secondary caries ( Kopperud et al, 2012 ; Opdam et al, 2014 ; Astvaldsdottir et al, 2015 ). Generally, secondary caries occur on the tooth after composite resin filling because oral biofilm bacteria are more likely to accumulate on the surface of resin restorations, leading to demineralization of dental hard tissues due to acid production, thus destroying the tooth structure and further providing a way for bacterial invasion ( Arun et al, 2021 ). Since secondary caries limit the lifetime of composite resin, it is urgent to endow composite resin with antibacterial properties and remineralizing capability.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, to combat secondary caries, numerous efforts have been devoted to synthesizing various antibacterial monomers with quaternary ammonium salts or incorporating antibacterial drugs/fillers [e.g., chlorhexidine, fluoride, zinc oxide (ZnO), and silver (Ag)] into the resin matrix to improve the antibacterial properties ( Cheng et al, 2012 ; Zhang et al, 2014 ; Cocco et al, 2015 ; Farrugia and Camilleri, 2015 ; Arun et al, 2021 ). However, the antibacterial effect of Ag- or ZnO nanoparticle (NP)-based composite resins has been reported not to be long-lasting, and the release of antibacterial agents (e.g., monomer/drug/Ag + ) would impair the mechanical properties and increase the risk of damage to human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study done by Wang et al, it was reported that with the increase in the quantity of ZnO NPs, there was a decrease in the mechanical properties of dental composite resins, with the exception of flexural strength, which may be attributed to the agglomeration of the nanoparticles ( Wang et al, 2019 ). In a systematic review by Arun et al, on the anti-bacterial properties of composite material incorporated with ZnO NPs, it was concluded that the material is unlikely to present a clinical advantage due to the short lifetime of anti-bacterial properties and the poor results against multi-species biofilms ( Arun et al, 2021 ).…”
Section: Applications Of Zinc Oxide Nanoparticles In Dentistrymentioning
confidence: 99%
“…The outstanding antimicrobial activity of the PCL/CS/ZnO composite coating was due to the synergistic antimicrobial properties of CS and ZnO NPs. This result in the production of reactive oxygen species (ROS) like H 2 O 2 , where CS electrostatically binds to the bacterial cell wall while ZnO NPs interact with protein membrane, resulting in the intracellular released material and perforated cell membrane [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Antibacterial Studiesmentioning
confidence: 99%